Determinan Financial Distress Pemerintah Daerah Provinsi di Indonesia - Yeni Widianingsih; Evada Dewata; Yuli Antina Aryani (JAF (Journal of Accounting and Finance), 2025)
The research team behind this study set out to determine how financial distress is influenced by three key financial indicators: regional financial independence, debt ratio, and profitability ratio. Using data collected over a five-year period (from 2018 to 2022), this research analyzed 170 samples from 34 provinces in Indonesia. Panel data regression is the analytical technique used. The Random Effect Model is used for the purpose of panel data estimation. This research found that although the debt ratio and profitability ratio significantly impacted financial distress, partly regional financial independence did not. In order to create fiscal policies that are more stable and less prone to financial distress, the findings of this research help the provincial government make strategic choices about regional financial planning.